Mathematics Education Students' Understanding of Exponent Concepts Based on Cognitive Style - Hikmahturrahman, Hikmahturrahman; Tamu, Suhardiman Darson; Yunus, Nosva Adam; Hasan, Febiyanti R.; Masaniku, Rizal (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
This study aims to explore the understanding of the concept of exponents of mathematics education students in terms of cognitive style. This type of research is qualitative with a case study approach. The subjects in this study were 2 mathematics education students consisting of 1 student with reflective cognitive style and 1 student with impulsive cognitive style. The instruments used in this study were 2 items of exponent problem solving and interview guidelines. The results showed that Reflective Cognitive Style Subjects were able to fulfill all indicators of understanding the concept of exponents, namely indicators of exponent problem solving, identifying positive, negative, and zero exponents, using exponent rules, understanding roots and fractions as exponents, and identifying and correcting exponent misconceptions. Meanwhile, Impulsive Cognitive Style Subjects were only able to fulfill 4 indicators of understanding the concept of exponents. Impulsive Cognitive Style Subjects were not able to fulfill the indicators of identifying and correcting exponent misconceptions. The advantage in this study is to fill the gap in the literature by connecting the understanding of the concept of exponents and cognitive style variations. Furthermore, making mathematics education students as research targets. It offers novelty because their understanding of exponents has direct implications on how they teach the concept in the future.